Odpowiedzi

2010-03-03T20:13:12+01:00
8)x=14
1)x=12
3)x=10
4)x=12
6)x=21
7)x=11
Najlepsza Odpowiedź!
2010-03-03T20:13:42+01:00
1)2(x-1) - 3(1+3x)= 3x- 7(6+x)-5
2x-2-3-9x=3x-42-7x-5
-7x-5=-4x-47
-7x+4x=-47+5
-3x=-42
x=14

2)6-0.25x= 0.75x - 6
-0,25x-0,75x=-6-6
-1x=-12
x=12

3)-2(x-10) - x= 2(x- 15)
-2x+20-x=2x-30
-3x+20=2x-30
-3x-2x=-30-20
-5x=-50
x=10

4) 2(x+5)+4= 2(x-3)+ x
2x+10+4=2x-6+x
2x+14=3x-6
2x-3x=-6-14
-x=-20
x=20

6) -15 - 5(2x-8)= 59- 4(3x - 2)
-15-10x+40=59-12x+8
-10x+25=67-12x
-10x+12x=67-25
2x=42
x=21

7) 4x- 3[2(x-1) + 5]= 4x - 3(x+9) - 15
4x-6(x-1)-15=4x-3x-27-15
4x-6x+6-15=x-42
-2x-x=-42+9
-3x=-33
x=11
1 5 1